Laboratory simulation of the surface erosion of solar glass mirrors. (August 2015) - Karim, M.; Naamane, S.; Delord, C.; Bennouna, A.
Highlights: Surface erosion of glass mirrors. Identification of the influencing parameters. Laboratory simulation of surface erosion in sand blower open circuit machine. Inputs parameters chosen according to natural exposure site. Evaluation of the effect of influencing parameters on surface erosion. Abstract: During their functioning in concentrated solar power plant – CSP, Glass mirrors are exposed to several climate conditions that cause their degradation. Surface erosion is among mechanical degradation phenomena that can alter mirrors surface and cause a decrease of the overall performance of the CSP plant. Several parameters are influencing this degradation phenomenon, namely the impact speed, the impact angle and the erosive sand particles properties. In this study, we proceed by simulation tests to investigate the effect of surface erosion phenomenon on thin glass mirrors. In order to be representative of the natural degradation phenomenon, the inputs parameters are chosen according to collected data from two different sites in Morocco. Results of simulation tests analysis indicate that the loss in specular reflectance increases with the impact speed. By analyzing the effect of the impact angle, it was discovered that the maximum surface erosion is observed at normal impact angle of 90°. Concerning the effect of sand particles properties on optical degradation, it was found that this latter increases by increasing the sand particle's size which increase the erosion surface rate. In addition, it was shown that the sand particle's sharpness presents a precursor for surface erosion phenomenon.